2022
DOI: 10.1007/s10554-021-02494-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Agatston score acquired with photon-counting detector CT and energy-integrating detector CT: ex vivo study of cadaveric hearts

Abstract: The purpose of this study was to compare the correlation and agreement between AS derived from either an energy-integrating detector CT (EID-CT) or a photon-counting detector CT (PCD-CT). Reproducibility was also compared. In total, 26 calcified coronary lesions (from five cadaveric hearts) were identified for inclusion. The hearts were positioned in a chest phantom and scanned in both an EID-CT and a prototype PCD-CT. The EID-CT and PCD-CT acquisition and reconstruction parameters were matched. To evaluate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Consequently, it is crucial to authenticate the applicability of this method in relation to the PCD-technology. Although there were only 14 patients with a positive AS, the comparison between EID-CT and PCD-CT showed good correlation and agreement, confirming previous results (39). To explore any over/underestimation of the AS, the PCD-CT data were reconstructed as 70 keV and 80 keV VMIs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, it is crucial to authenticate the applicability of this method in relation to the PCD-technology. Although there were only 14 patients with a positive AS, the comparison between EID-CT and PCD-CT showed good correlation and agreement, confirming previous results (39). To explore any over/underestimation of the AS, the PCD-CT data were reconstructed as 70 keV and 80 keV VMIs.…”
Section: Discussionsupporting
confidence: 88%
“…To explore any over/underestimation of the AS, the PCD-CT data were reconstructed as 70 keV and 80 keV VMIs. VMI 70 keV showed a tendency for overestimation of the AS, whereas VMI 80 keV showed a tendency to underestimate the AS for the PCD-CT (39). Therefore, in terms of the AS, the best match between EID-CT and PCD-CT is likely somewhere between these two keV-levels, although larger studies are needed to validate this result.…”
Section: Discussionmentioning
confidence: 94%
“…of 2 was about 3%. Skoog et al 37 showed high agreement between PCD- and energy-integrating detector CT–derived CACS using virtual monoenergetic reconstructions at 72 keV in a study of cadaveric hearts.…”
Section: Discussionmentioning
confidence: 97%
“…19,31 Several ex vivo and in vivo studies already demonstrated the feasibility of accurate CACS with PCD CT using TNC scans. 21,[32][33][34][35][36][37] Emrich et al 20 evaluated this VNI algorithm on PCD CCTA data and showed high accuracy using postprocessing settings at 70 keVand QIR 2. This is in line with the results of the present study that additionally confirms excellent correlation and agreement of CACS VNI with CACS TNC at every investigated VMI level from 55 to 80 keV and every QIR level from strength 1 to 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas dual-energy-based VNC images are obtained using 2-material separation into soft tissue and iodine, 7,8 PCD enables multimaterial differentiation, including the separation between iodine and calcium 19,31 . Several ex vivo and in vivo studies already demonstrated the feasibility of accurate CACS with PCD CT using TNC scans 21,32–37 . Emrich et al 20 evaluated this VNI algorithm on PCD CCTA data and showed high accuracy using postprocessing settings at 70 keV and QIR 2.…”
Section: Discussionmentioning
confidence: 99%